Does passive smoke exposure trigger acute asthma attack in children? - (:unkn) unknown (My University, 2003)
The relationship between asthma and passive smoking has been well established. However, it is still not clear whether an acute asthma attack can be induced by acute smoke exposure. The specific aims of this study were: 1- To assess the degree of smoke exposure through urinary cotinine levels in asthmatic children during and 4 weeks after asthma attacks and, 2- To evaluate the reliability of parental questionnaires in asthmatic children by comparing the data obtained from cotinine measurements and parental reports. Thirty-two consecutive asthmatic children who were admitted to the emergency clinic were included in the study. Parents were asked to complete a questionnaire about their smoking habits and housing conditions. Urinary cotinine and creatinine levels were measured in children during and 4 weeks after the acute asthma attack. The mean age of the patients was 5.7 +/- 3.2 years. The mean attack rate was 3.5 +/- 3.8 per year. Thirty-eight percent of the patients were taking no preventive treatment. In 80 % of patients, urinary cotinine and creatinine ratios (CCR) were significantly above the non-exposed, non-smoker levels. However, CCR levels during acute asthma attacks were not higher than those measured 4 weeks after the acute attack (314.6 +/- 299.1 vs. 203.8 +/- 165.2 ng/mg respectively, p > 0.05). Although parental reports of passive smoke exposure was 71 %, CCR levels revealed that 81 % and 97 % of children were exposed to passive smoke during acute attacks and asymptomatic periods, respectively. In conclusion, although the proportion of children with acute asthma attacks who were exposed to passive smoking was high, the degree of passive smoke exposure was not higher during acute attacks. Parental questionnaires were found to be unreliable in reporting passive smoke exposure in asthmatic children during acute attacks.
Keywords: Adult; Female; Humans; Surveys and Questionnaires; Turkey; Adolescent; Infant; Male; Biomarkers; Child; Parents; Child, Preschool; Tobacco Smoke Pollution; Smoking; Prospective Studies; Creatinine; Acute Disease; Asthma; Cotinine; Emergencies